If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-3+6x=3x+17
We move all terms to the left:
x-3+6x-(3x+17)=0
We add all the numbers together, and all the variables
7x-(3x+17)-3=0
We get rid of parentheses
7x-3x-17-3=0
We add all the numbers together, and all the variables
4x-20=0
We move all terms containing x to the left, all other terms to the right
4x=20
x=20/4
x=5
| 2x.3x.4x=24 | | 12x^2+2x-8=0 | | -41=-56-b | | 3x+4+5x+6=42 | | 294+.30x=x | | –3(n+2)=15 | | 3x(x-5)+7x=5(3-x) | | 3a2=36 | | 2x/5+5x=16/16 | | .525/x=0.25 | | -7(-2v+3)-2v=6(v-5)-7 | | 8-7x=-6-9 | | 2x3x4x=24 | | 19y+39=96 | | y-4=2y | | 3x+17=x+17+2x | | 2(4n+6)=n | | -6=14-w | | 14=h/1.5 | | 2y+56=180 | | -3(2x-3)=21 | | -4+2v-8=5v+9 | | -12=22+n | | 2(3x+7)(x-1)=0 | | 25(x+3)=2(2x+1) | | 4n-2=n | | -18+22=-4(x+9) | | 40=-2(5x+20) | | 3+5=16a | | w–14=-6 | | 0.75x+18=41 | | 6x=6.9 |